1997
DOI: 10.1076/apab.105.1.19.13152
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Acid Neutralization Capacity of Saliva and Gastro-Oesophageal Reflux

Abstract: Saliva is an important factor in neutralization of oesophageal acid exposure, clinically manifested as gastrooesophageal reflux (GOR). The aim of this study is to compare the composition and the "capacity in acid neutralization" (CAN) of saliva in controls and patients suffering of GOR. We compared the composition of saliva from 56 patients who had symptoms of GOR with that of saliva from 20 healthy control subjects. After a standardized 24-hour period of pH-monitoring, 39 patients had normal pH reflux scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Saliva is an important determinant of esophageal acid neutralization in GER (8). We demonstrated that there is a significant correlation between ED50 and a nocturnal fall in salivary pH (ΔpH), but not initial salivary pH measured during the daytime, in both healthy and mildly asthmatic subjects.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Saliva is an important determinant of esophageal acid neutralization in GER (8). We demonstrated that there is a significant correlation between ED50 and a nocturnal fall in salivary pH (ΔpH), but not initial salivary pH measured during the daytime, in both healthy and mildly asthmatic subjects.…”
Section: Discussionmentioning
confidence: 85%
“…Dental erosion, which is caused by acid exposure in GER, shows an association with acidity in saliva (7). The initial salivary pH is correlated with pH in the lower esophagus and is higher in GER subjects than in control subjects (8). In addition, Katz et al (9) ORIGINAL A nocturnal decline of salivary pH associated with airway hyperresponsiveness in asthma Naoto Burioka 1 , and Eiji Shimizu detected nocturnal gastric acid breakthrough (NAB), defined as nighttime periods exceeding 1 h with a gastric pH below 4.0, in 67% of normal subjects ; and it was previously reported that there is a nocturnal decline of salivary pH in healthy subjects (10).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The collected saliva samples were immediately frozen at -20 ° C. Later they were thawed and titrated with 0.1 N HCl from initial pH to pH 7.0, 5.5, 4.0 and 3.0 using 4 g of saliva for each analysis [Bouchoucha et al, 1997] (Microlab , Bonaduz, Switzerland). Buffering capacity ( ␤ ) was calculated as ␤ = ͉ ⌬ C/ ⌬ pH ͉ , where ⌬ C is the amount of the acid used and ⌬ pH is the change in pH caused by the addition of the titrator.…”
Section: Determination Of the Secretion Rate And Titration Of Saliva mentioning
confidence: 99%
“…Accessible body fluids such as saliva represent an interesting medium for the realization of body-sensing, as these fluids also contain important personal physiological information [13][14][15][16][17][18][19][20]. Continuous monitoring of pH in saliva would be extremely beneficial for maintaining healthy mouth conditions, e.g., degradation of tooth enamel [21] and detection of Gastroesophageal Reflux Disease (GERD) [22][23][24], as well as drug activity, as in some cases this can depend on saliva pH [17].…”
Section: Introductionmentioning
confidence: 99%